2016
DOI: 10.1111/tme.12370
|View full text |Cite
|
Sign up to set email alerts
|

Combined cell index in assessing blood donor iron stores

Abstract: Study results confirmed the satisfactory diagnostic value of CCI in detecting depleted iron stores in blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that ATO is absorbed into the bloodstream, where it binds with HGB and is rapidly distributed to tissues and organs [12,13]. Routine clinical erythrocyte analyses include seven parameters [14]: RBC count, HGB, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular HGB (MCH), mean corpuscular HGB concentration (MCHC), and RDW. The RBC count and HGB are absolute values that serve as important indicators of anemia, whereas the HCT expresses RBC as a percentage of the whole blood volume, reflecting the ratio of RBC to plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ATO is absorbed into the bloodstream, where it binds with HGB and is rapidly distributed to tissues and organs [12,13]. Routine clinical erythrocyte analyses include seven parameters [14]: RBC count, HGB, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular HGB (MCH), mean corpuscular HGB concentration (MCHC), and RDW. The RBC count and HGB are absolute values that serve as important indicators of anemia, whereas the HCT expresses RBC as a percentage of the whole blood volume, reflecting the ratio of RBC to plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Sir, Iron deficiency in blood donors is an important adverse consequence of frequent blood donations (Vuk et al, 2017). Numerous studies have been published so far with the aim of reducing this risk and improving the well-being of blood donors.…”
Section: Influence Of Cigarette Smoking On Haemoglobin Concentration mentioning
confidence: 99%
“…3,4,17,18 Our study has shown a moderate correlation between serum ferritin and RDW, a relationship that has not been well described before, except the idea of using combined (red) cell index. 19 Measurement of the RDW comes at no additional cost when a CBC is performed.…”
Section: Discussionmentioning
confidence: 99%